The epistemological position of researchers in education policy: theoretical debates about the neo-Marxist, pluralist and post-structuralism perspectives - Tello, Cesar; Mainardes, Jefferson (Education Policy Analysis Archives, 2012)
This article presents partial results of an inquiry that aims at characterizing and describing epistemological perspectives applied in research on educational policy in Latin America. It presents an analyses of the research carried out in six Latin American countries and published between 1993-2001. The references to authors in this paper as ‘referring authors’ where identified and these authors can be included in specific epistemological perspectives. Thus, the paper presents discussions on the neo-Marxism and ‘Globally Structured Agenda for Education’ developed by Roger Dale, epistemological pluralism and ‘perspectivism’ from the Social Cartography of Rolland Paulston, and post-structuralism and ‘policy cycle approach’ of Stephen Ball. However, in all papers analyzed the use of theoretical frameworks were posed in terms of methodology, isolated from its epistemological foundations in which they were produced. On the other hand, the analysis could not clearly elucidate the presence of epistemological positioning of the researchers even when the authors of the papers analyzed were applying those theoretical frameworks. Methodologically, the research presented in this paper was carried out from a qualitative and descriptive-analytical perspective, based on secondary sources of a bibliographical nature. After the conceptual description of each of epistemological perspectives, the paper concludes that the epistemological perspectives cannot be applied in a ‘pure’ way in the field of educational policy. However, this assumption does not negate the need for the presence of the researcher's epistemological positioning.